Associations among education, age, and the dementia with Lewy bodies (DLB) metabolic pattern: A European‐DLB consortium project. Issue 8 (2nd February 2021) - Bauckneht, Matteo; Chincarini, Andrea; Brendel, Matthias; Rominger, Axel; Beyer, Leonie; Bruffaerts, Rose; Vandenberghe, Rik; Kramberger, Milica G.; Trost, Maja; Garibotto, Valentina; Nicastro, Nicolas; Frisoni, Giovanni B.; et al.
Abstract: Introduction: We assessed the influence of education as a proxy of cognitive reserve and age on the dementia with Lewy bodies (DLB) metabolic pattern. Methods: Brain 18F‐fluorodeoxyglucose positron emission tomography and clinical/demographic information were available in 169 probable DLB patients included in the European DLB‐consortium database. Principal component analysis identified brain regions relevant to local data variance. A linear regression model was applied to generate age‐ and education‐sensitive maps corrected for Mini‐Mental State Examination score, sex (and either education or age). Results: Age negatively covaried with metabolism in bilateral middle and superior frontal cortex, anterior and posterior cingulate, reducing the expression of the DLB‐typical cingulate island sign (CIS). Education negatively covaried with metabolism in the left inferior parietal cortex and precuneus (making the CIS more prominent). Discussion: These findings point out the importance of tailoring interpretation of DLB biomarkers considering the concomitant effect of individual, non–disease‐related variables such as age and cognitive reserve.